2011
DOI: 10.1111/j.1440-1797.2010.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral lumbar X‐ray assessment of abdominal aortic calcification in Australian haemodialysis patients

Abstract: AAC detected by lateral lumbar X-ray is highly prevalent in our cohort of Australian HD patients and is associated with cardiovascular disease, increasing age and duration of HD. This semi-quantitative method of determining vascular calcification is widely available and inexpensive and may assist cardiovascular risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 44 publications
5
33
0
4
Order By: Relevance
“…Factors such as presence of diabetes, hypertension, prior history of cardiovascular disease, and longer dialysis vintage were also significantly associated with higher AAC score. These findings were similar to prior crosssectional study results, 5,14 which showed that the most contributive factors for vascular calcification were patient's age, dialysis vintage and prior history of CAD.…”
Section: Discussionsupporting
confidence: 91%
“…Factors such as presence of diabetes, hypertension, prior history of cardiovascular disease, and longer dialysis vintage were also significantly associated with higher AAC score. These findings were similar to prior crosssectional study results, 5,14 which showed that the most contributive factors for vascular calcification were patient's age, dialysis vintage and prior history of CAD.…”
Section: Discussionsupporting
confidence: 91%
“…Abdominal aortic calcification (AAC) was assessed using a previously validated 24-point scale [17]. All subjects were assessed independently by two investigators blinded to patient demographics and serum markers.…”
Section: Methodsmentioning
confidence: 99%
“…Associations between age, DM and CVD with the severity of VC in different CKD populations have been described previously . In CKD stage 5D patients, the relationship between dialysis vintage and the severity of VC has been documented . In KT recipients, dialysis vintage has been shown to predict the progression of VC in the early post‐transplantation period .…”
Section: Discussionmentioning
confidence: 71%
“…4,[19][20][21] In CKD stage 5D patients, the relationship between dialysis vintage and the severity of VC has been documented. 4,15,19,21 In KT recipients, dialysis vintage has been shown to predict the progression of VC in the early post-transplantation period. 22 There has been no report on the relationship between dialysis vintage and the severity of VC in long-term-KT recipients until the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation